Factorial Big Data Analytics for Sustainable Public Procurement Practices - Mbhele, Thokozani Patmond; Salomo, Emilia Ndeshipanda (Journal of Cultural Analysis and Social Change, 2026)
The epitome of sustainable public procurement practices aligns with the principles of transparency, integrity, competitiveness, and efficiency, underpinned by the growing adoption of big data analytics capabilities. Big data analytics (BDA) enhances supply chain visibility, operational efficiency, and risk management; however, it has become evident that public supply chains in developing nations require robust digital infrastructure to effectively leverage the potential benefits of BDA. The research objective is to establish the effective role of Big Data Analytics (BDA) in enhancing sustainable public procurement practices (SPPP), aligning with the objectives of the Namibian Procurement Act 2015. The research further evaluates the factors impacting the technological, organisational and environmental context of public procurement principles through data-driven insights on the view of economic constraints and inequalities. The descriptive quantitative research design is rooted in a positivist perspective, focusing on an empirical case study of Namibia to assess the impact of BDA within the Technology-Organisation-Environment (TOE) framework. The research design employs a descriptive case study, enabling the exploration of factorial interrelationships. Diverse perspectives are integrated via stratified sampling, resulting in a sample size of 270 administered for data collection. Inferential statistics, including multivariate analysis, were used to analyse the data. The study revealed enhanced public procurement practices following the enactment of the Public Procurement Act 2015. ICT infrastructure, data quality, and system scalability are pivotal for BDA integration, despite hindrances such as leadership commitment, procurement capacity, procedural complexities, and resource constraints, which impede the shift towards sustainable procurement. These findings culminate in a TOE framework, which suggests that BDA's adoption offers significant strategic value, including improved decision-making, increased efficiency, enhanced transparency, and improved supplier performance in procurement. BDA's strategic effective role/value influences its adoption, leading to the transformation of sustainable public procurement practices in Namibia. This model systematically outlines the impact of BDA adoption on public procurement, showcasing how the TOE factors shape BDA's success in achieving SPPP. This research provides policymakers, public procurement professionals, and technology providers with practical insights to enhance the strategic value of BDA for sustainable procurement. This study contextualises the interplay of TOE factors for BDA adoption in public procurement for developing nations.